Incidence of Catastrophic Health Expenditures Amongst Hospitalized Neonates in Ekiti, Southwest Nigeria - Ogundare EO; Taiwo AB; Olatunya OS; Afolabi MO (Dove Medical Press, 2022)
Ezra O Ogundare,1,2 Adekunle B Taiwo,3 Oladele S Olatunya,1,2 Muhammed O Afolabi4 1Department of Paediatrics, Ekiti State University, Ado-Ekiti, Nigeria; 2Department of Paediatrics and Child Health, Ekiti State University Teaching Hospital, Ado Ekiti, Nigeria; 3Department of Paediatrics, Zankli Medical Services, Abuja, Nigeria; 4Department of Disease Control, Faculty of Infectious and Tropical Diseases, London School of Hygiene & Tropical Medicine, London, UKCorrespondence: Ezra O Ogundare, Department of Paediatrics, Ekiti State University, Ado-Ekiti, Nigeria, Tel +234-803-501-7416, Email ogundarezra@gmail.comBackground: Neonatal illnesses require huge spending due to prolonged hospital stay. The management of these illnesses is usually financed by individual families which in most instances are living below the poverty line. This healthcare financing method can readily push families into catastrophic spending on health.Aim: To ascertain the average cost of managing common neonatal illnesses and the financial burden, it constitutes to families in Ekiti State, southwest Nigeria.Methods: We conducted a cross-sectional study on the out-of-pocket spending involved in managing neonates admitted into and discharged from the SCBU of the Ekiti State University Teaching Hospital, Ado-Ekiti, southwest Nigeria. Data collected included the monthly family income, the money spent on drugs, laboratory investigations and the hospital bill using a purposely designed structured questionnaire. Healthcare spending greater than 10% of the overall family income was described as catastrophic health spending (CHS).Results: The medical bills for most (95%) of the 119 study participants were paid through the out-of-pocket means and 81.5% of the families spent more than 10% of their monthly earnings (CHS) to settle medical bills. Close to 50% of the families belonged to the lower social economic class. The median (IQR) duration of hospital stay was 2.75 days (3.0- 8.0). The median (IQR) total expenditure was N24,500.00 (N13,615.00-N41,487.50). The median (IQR) expenditure for the treatment of prematurity was highest at N55,075.00 (USD 133.10) [N27,350.00 (USD 66.10)-N105,737.50 (USD 255.53)] and more than 60.5% of the expenses was on hospital utilities and consumables. The length of hospital stay showed a robust positive correlation with the total hospital bill (r = 0.576, P < 0.001).Conclusion: Neonatal illnesses put many households at risk of catastrophic health spending. There is need for increased government investment in health and extension of the health insurance scheme to all the citizens of the country.Keywords: neonatal illness, out-of-pocket spending, catastrophic health spending, Nigeria